Identifying the Motivational Factors Influence The Consumption of Buying Items in Game Defences of The Anchient 2 - Putri, Rieda Anindita; Setyabudi, Djoko; Purbaningrum, Dwi; Rahmiaji, Lintang Ratri (Interaksi Online, 2016)
Game is one form of implementation of the technological advances in the realm ofcommunication media. The game can be used as a medium conveys messages and allow forfeedback from the message. Game is also designed as a means of entertainment to fill inspare time made universal. DotA2 is multiplayer game with the highest user in Indonesia.The game is themed multiplayer online battle arena video games, with the format of threedimensional(3D). In addition to playing the game, players can buy items that are in the gameas a complementary game. Player purchase with virtual money and buy in a virtual store.Amount DotA2 spent in the virtual shop is amazing. In fact, the goods they purchase invirtual shop could not be held and owned real, whereas money spent not a little.This study aims to determine the motivating factors that influence purchasingbehavior items in the game Defense of the Ancients 2. This quantitative explorative studycollecting primary data from 100 people with a research instrument questionnaire. Analysisof the data used is the technique of factor analysis. A total of 12 factors have been tested withKMO and Bartlett's Test unknown value is 0.963 with 0.000 significance. Then through acalculation model of Principal Component Analysis (PCA) obtained two groups of factorsthat includes 12 factors tested, in other words, all factors tested escaped. All of these factorscontributed 77.346 per cent of the purchase motivation in Game DotA2 items.Personal Interest Factor is the most powerful motivating factor. These factors areknown to contribute as much as 65.745%. This factor is labeled Personal Interest Factorbecause it consists of motivated interest in the items on DotA2, the ease of access to thevirtual shop DotA2, and feelings of pleasure that is in the player when transacting in thevirtual shop. The fourth main variables of the next factor is the decoration, benefits,relatedness, and fun including the Pleasure Factor which is a form of interest because it givespleasure.